THE GUT MICROBIOME REGULATES EFFICACY OF SULFASALAZINE THERAPY FOR SPONDYLOARTHRITIS IN INFLAMMATORY BOWEL DISEASE. (26th January 2023) - Lima, Svetlana; Rupert, Amanda; Jin, Wenbing; Viladomiu, Monica; Pires, Silvia; Woo, Viola; Putzel, Gregory; Marderstein, Andrew; Funez-dePagnier1, Gabriela; Yang, Wei; Guo, Chun-Jun; Scherl, Ellen; et al.
Abstract: Joint inflammation, or spondyloarthritis (SpA ), is the most common extra-intestinal manifestation of inflammatory bowel disease (IBD ), but the specific role for therapies targeting SpA is not well defined. One of the earliest medications used for the treatment of IBD is sulfasalazine (SAS ). SAS is a prodrug composed of two chemical moieties, the anti-inflammatory 5-aminosalicilate and the antibiotic sulfapyridine. The efficacy of SAS in peripheral arthritis is thought to depend on its "antibacterial" properties, however the impact of SAS on the IBD-SpA microbiome and how it may improve extra-intestinal symptoms is unknown. Therefore, our study aims to diagnostically evaluate the role for the fecal microbiome in clinical response to SAS therapy and identify microbial and immunologic therapeutic targets associated with clinical response. We have designed an observational study to longitudinally follow IBD patients with SpA who have a medical indication for SAS therapy. Clinical data and fecal samples from 22 patients were collected before initiation of SAS and at week 12 after initiation of SAS. Eleven IBD-SpA patients were concomitantly enrolled as controls and followed by 12 weeks. Metagenomic sequencing was used to define the effect of SAS on the IBD-SpA fecal microbiome and to evaluate its relationship with improvement in joint symptoms. Mouse models and in vitro assays were used to test the sufficiency of the SAS effect observed in patients. The fecal microbiome of SAS-responders was distinct from that observed in non-responders and 6 pre-treatment microbial markers (including the short chain fatty acid (SCFA ) producer Faecalibacterium prausnitzii ) predicted SAS-response (AUC = 0.9). Fecal metabolome of SAS responders had lower thymine and higher deoxyuridine compared to non-responders consistent with evidence of a folate trap in response to SAS treatment. SAS therapy in SPF mouse-model of chemically-induced colitis alleviated colitis in GPR 109a-dependent fashion consistent with a synergistic role for SCFA. In vitro assays revealed SAS direct regulation of F. prausnitzii metabolic function and butyrate synthesis. CONCLUSIONS: Collectively, these findings highlight the potential role for microbial diagnostics to improve SAS efficacy, and drug modulation of microbial markers to potentiate therapy for IBD patients with SpA.